Medusavirus Ancestor in a Proto-Eukaryotic Cell: Updating the Hypothesis for the Viral Origin of the Nucleus - Takemura, Masaharu (Frontiers in Microbiology, 2020)
The mechanistic evolutionary origin of the eukaryotic cell nucleus remains unknown. Among several plausible hypotheses, the most controversial is that large DNA viruses, such as poxviruses, led to the emergence of the eukaryotic cell nucleus. Several recent findings, including the discovery of a nucleus-like structure in prokaryotic viruses and prokaryotes possessing nucleus-like inner membranes, suggest genomic DNA compartmentalization not only in eukaryotes but also in prokaryotes. The sophisticated viral machinery of mimiviruses is thought to resemble the eukaryotic nucleus: DNA replicates both inside the viral factory and nucleus, which is at least partially surrounded by membranes and is devoid of ribosomes. Furthermore, several features of the recently identified Acanthamoeba castellanii medusavirus suggest that the evolutionary relationship between ancestral viral factory and eukaryotic nucleus. Notably, Ran, DNA polymerase, and histones show molecular fossils of lateral transfer of nuclear genes between the virus and host. These results suggest viral innovation in the emergence of the eukaryotic nucleus. According to these results, a new scenario explaining the origin of the eukaryotic nucleus from the perspective of viral participation is proposed. This new scenario could substantially impact the study of eukaryogenesis and stimulate further discussion about viral contributions to the evolution of the eukaryotic nucleus.